(untitled) (Medicine Today, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a rapidly rising public health concern worldwide and a major burden in Bangladesh due to urbanization, lifestyle changes, and socioeconomic disparities. The rising prevalence rates of T2DM pose a threat to overwhelm an already overburdened health system. The current article aims to highlight the rising burden of T2DM in Bangladesh and assess existing disease management policies in the context of a health system burden and equity. Materials and Methods: A qualitative study was conducted by reviewing various journal articles and reports published by international health organizations and national policies. The findings and evidence on various aspects of T2DM in Bangladesh were synthesized under various themes and subheadings. Discussion: Based on the findings, it is evident that Bangladesh has made considerable progress in developing national policies to address non-communicable diseases. However, there is a need to address various challenges and gaps in primary care services and high out-of-pocket expenditure. Socioeconomic disparities and gender disparities also need to be addressed. Furthermore, mental health comorbidities need to be addressed to improve disease outcomes. Conclusion: The problem of T2DM in Bangladesh is an emerging public health crisis that requires a concerted, equitable, and multi-faceted response. Strengthening primary care, mental health care, affordability, and community-based prevention are critical steps in controlling the rising tide of T2DM. Medicine Today 2026, Vol.38 (1): 148-151